Representações sociais de alunos de uma instituição de ensino superior sobre o bom e o mau professor - Guimarães, Cidclei Santos (2016)
This work investigated through the word of the students, the way they see the work of their teachers and how this look can point out ways to improve the practice of teaching through teacher training. The objective of this research was to understand the social representations of Good and Bad Teacher shared by undergraduate students, in order to analyze its relations with the teaching profession in order to reflect on the education offered in higher education from the perspective of articulated vocational training and oriented towards citizenship that should be the result of a process of transformation of social relations today. Therefore, the specific objectives were to investigate the social representations of students of Advertising - Advertising and Paulista University Law - UNIP on the "Good and Bad Teacher"; describe the social representations of registered students in research; identify features of "Good and Bad Teacher"; identify the elements that make up the central core of these representations. The theoretical and methodological plan was supported by the Theory of Social Representations of Moscovici and contributions of Jean Claude Abric and other scholars whose relevance is undeniable, for discussion and analysis of theoretical and empirical categories. We used the free association technique through a structured questionnaire as procedure and methodological tool. The results indicate that these representations are formed mainly by normative and functional elements, linked to cognitive functions, socio-cultural and ethical professional practice, while guiding the teaching social practice, whose core has at its center the words "Good Teacher" and "Bad Teacher." The results oportunizaram reflection on the need for attention to the specificities of teacher training for higher education, highlighting the work of the teacher as subject responsible, committed to the training of students, focusing on their learning and may subsidize study activities, monitoring and evaluation of teaching practice in higher education institutions, allowing corroborate even with the institutionalization of training and educational upgrading programs, and reference other scientific research